2022
DOI: 10.25270/wmp.2022.5.1424
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL RESEARCH Virtual Events in the Era of COVID-19: Perspectives From a Virtual Interdisciplinary Wound Care Symposium

Abstract: BACKGROUND: The coronavirus disease-19 pandemic has created changes in the way medicine is practiced. The move to virtual conferencing to avoid mass gatherings is a significant change to how health care professionals meet, discuss current trends, and share research. METHODS: Data from exit polls conducted after annual wound care symposiums were reviewed. Physicians, nurses, podiatrists, and other health care professionals attended. Respondents were asked to comment and reflect on their experiences of attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This facility allows conference attendees to maximize their learning. Results from one study among virtual conference attendees found that 83% of respondents planned to visit post‐conference online materials 3 . As we move back towards more in‐person events, it is important to reflect on the lessons learned from holding virtual events, in order to decide which aspects should remain.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This facility allows conference attendees to maximize their learning. Results from one study among virtual conference attendees found that 83% of respondents planned to visit post‐conference online materials 3 . As we move back towards more in‐person events, it is important to reflect on the lessons learned from holding virtual events, in order to decide which aspects should remain.…”
mentioning
confidence: 99%
“…Instant messaging via online conference platforms has been proposed as a useful tool to substitute these in-person interactions. 3 However, the effect to which it does this is questionable. While breakout rooms offer a virtual space where interactions can take place, these interactions may be less effective than face-to-face meetings.…”
mentioning
confidence: 99%
See 2 more Smart Citations